Effects of vermicompost medium towards growth of ipomoea aquatica / Siti Nursabiha Md. Rahim - Md. Rahim, Siti Nursabiha (2017)
Vermicompost has been proved to have positive effects as a medium for plant growth. This study was to determine the most effective vermicompost medium for the growth of Ipomoea aquatica. There were three types of organic wastes used which are cow dung, vegetable waste and paper waste. All of these wastes were turn into vermicompost soil after 30 days vermicomposting and then were used as a soil media for Ipomoea aquatica growth. There were three types of vermicompost mediums which are cow dung, cow dung with vegetable waste and cow dung with paper waste. Each medium consist of 50% vermicompost soil and 50% natural soil and growth of Ipomoea aquatica in these medium were compared with control medium which consist of 50% natural soil and 50% commercial organic fertilizer. In this study, result showed the most positive growth was in the cow dung with vegetable waste medium.